Analysis of the Speed of Ap Chagi Kick Technique in Taekwondo Senior Athlete Dojang Garuda Satria Banjarbaru City - Ismi Cahya Marshanda; Norma Anggara; Akhmad Amirudin (Universitas Negeri Semarang, 2025)
This study aims to analyze the speed of Ap Chagi's kick technique in senior Taekwondo athletes Dojang Garuda Satria Banjarbaru City. Quantitative descriptive research using an experimental survey design was employed in this investigation. The sample consisted of 15 senior athletes selected using the purposive sampling technique. The measurement was carried out by counting the number of Ap Chagi kicks that were successfully made within 15 seconds using the stopwatch and the target kick. The results showed that of the 15 athletes tested, 5 people (33%) were in the